Islamic social centre : an Islamic architecture based on social-value expressed in the prophetic tradition - Parker, Mughsin (School of Architecture, Planning and Geomatics, 2016)
The influential role Islam as a religion has on its architecture has not been a recent interest of mine, but as a born Muslim, it has always been an area of research I wished to explore. The content of this paper is therefore not based only on theoretical research done, but also on a personal religious belief system. As the Quran and Hadith (prophetic tradition) plays an integral role in the life of a Muslim, the architecture we inhabit is a vital element in achieving an environment conducive to the practice of an Islamic lifestyle. As it is understood that Islam is a 'way of life', the intention of my research was not aimed at the design proposal of a religious institution such as the Mosque, but rather the idea of an Islamic Social Centre. The purpose of such a centre would not only be to serve the Muslim community, but also to engage the broader Muslim and non-Muslim community in creating a platform for the exchange of knowledge under the banner of Islam. The number of Muslims in South Africa, according to a recent survey, is approximately two million people, (MJC: 2005). Although it is not easy in a South African society, most of these Muslims adhere to a strict Islamic lifestyle. Given that leisure and recreation is a human necessity, South African Muslims are faced with a challenge. The challenge arises in the fact that current places of leisure or social activity do not cater for Muslims' needs, governed by Islamic Law. An example of this need would be the separation of the sexes in order to create an acceptable Islamic environment that would cater for religiously orientated activities. The requirement is thus for a place that would facilitate the needs of the contemporary Muslim while adhering to the conditions set out by Islamic Law. The preceding research documents involved the study of Islam in relation to the spatial implications it has on the lifestyle of a Muslim. This document shall clarify the impact Islam has on the design of the building by explaining its architectural relevance to the design thesis. The criteria that the design of the building will be checked against is the Quran and Hadith while making sure that the two sources do not contradict, which if be the case, the Quran shall take precedence. While the intention is not to design a Mosque, it is important to note that a Mosque should form part of the facility I propose in the design thesis, as it is integral in creating an Islamic environment.